CONSTRUCTING “CHINESE PHILOSOPHY” IN SINO-EUROPEAN CULTURAL EXCHANGE. - YIJIE, TANG (Journal of Chinese Philosophy)
The article discusses about the introduction of Chinese philosophy in to the west. The author tries to construct the Chinese philosophy using the Western philosophical framework and discusses its differences as well as the problems that would incur such as translation especially with words such as Qi which can have different meanings with no direct translation.